Pengaruh Keputusan Pendanaan, Keputusan Investasi, Kebijakan Dividen, Dan Arus Kas Bebas Terhadap Nilai Perusahaan - Muhammad Fadly Bahrun; Tifah Tifah; Amrie Firmansyah (Institut Bisnis dan Informatika Kesatuan, 2020)
This study examines the effect of funding decisions, investment decisions, dividend policies, and free cash flow on firm value. The samples used in this study are consumer goods industry companies listed on the Indonesia Stock Exchange (IDX) during 2016-2019. Based on purposive sampling, the selected sample is 34 companies, so that the total sample is 136 observations. Hypothesis testing is carried out using multiple linear regression analysis of panel data. The test results show that funding decisions positively affect firm value, while investment decisions do not affect firm value. This study also shows that dividend policy and free cash flow have a negative effect on firm value.